Media Access Control in Wireless Sensor Networks using Priority Index - Mallanagouda Patil; Rajashekhar C. Biradar (Institute of Advanced Engineering and Science, 2017)
As the nodes in Wireless Sensor Networks (WSNs) have limited power, energy conservation is essential at different layers of the protocol stack to prolong lifetime. In our previous work, ”Priority based slot allocation for media access in wireless sensor networks” (PSAWSN), probability based priority scheme is used to allocate slots to competing nodes. Limitations of this work include 1) It does not handle dynamic and variable slot allocation based on varying requirements of nodes. 2) Error control is not taken into account. To overcome these limitations, we propose a Medium Access Control scheme using Priority Index (MACPI) that generates Priority Index (PI) to allocate varying slots based on parameters: message length (ML), node energy (NE), number of requests (NR) and message urgency (MU). Models have been de- signed for all these parameters and an expert system is proposed that makes decisions based on collective knowledge of these parameters. Analysis and simulation results for various message sizes and error conditions show that there is an improvement in terms of energy efficiency, optimal message length and throughput compared to the ”Reliable data deliveries using packet optimization in multi-hop underwater sensor networks”(RDPSN).